Localized CO2-induced salt precipitation in unconsolidated saline porous media: Insights from quasi-2D flow cell experiments - Jonathan I. Mendez-Ruiz; Priscila E. Valverde-Armas; Daniela Olaya; Juan D. Quintero; Camilo A. Franco; Farid B. Cortés; Leonardo Gutierrez; Kristoffer Eikehaug; Jacquelin E. Cobos (Gas Science and Engineering, 2026)

Introduced ungulate browsing facilitates non-native tree invasions through enhanced compensatory growth and inducible defenses - Carolina Quintero; Romina D. Dimarco; Yamila Sasal; Gabriela Reiner; Daniela Nassini; Martín A. Nuñez; Juan Paritsis (Biological Invasions, 2026)

Gallein-Loaded Albumin Nanoparticles Prevent Amyloid-β–Induced Amyloidogenic APP Processing, Synaptic Loss, and Dendritic Pathology - Romina Soledad Almirón; Cecilia Tettamanti; Sofía Martinez; Magdalena Antonino; Paula Marmo; Ángela Debiagge; Delfina Toselli; Lucia Moro; Daniel Allemandi; Alfredo Lorenzo; Daniela Alejandra Quinteros; Elena Anahi Bignante (Molecular Neurobiology, 2026)

Multi-omics Quality Assessment in Personalized Medicine Through European Infrastructure for Translational Medicine (EATRIS): An Overview - Patricia Alonso-Andrés; Davide Baldazzi; Qiaochu Chen; Elisa Conde Moreno; Lorena Crespo-Toro; Kati Donner; Petr Džubák; Sara Ekberg; Maria Laura García Bermejo; Daniela Gasparotto; Bishwa Ghimire; Jolein Gloerich; et al. (Phenomics, 2025)
Molecular characterization of a biological sample, e.g., with omics approaches, is fundamental for the development and implementation of personalized and precision medicine approaches. In this context, quality assessment is one of the most critical aspects. Accurate performance and interpretation of omics techniques is based on consensus, harmonization, and standardization of protocols, procedures, data analysis and reference values and materials. EATRIS, the European Infrastructure for Translational Medicine ( www.EATRIS.eu ), brings together resources and services to support researchers in developing their biomedical discoveries into novel translational tools and interventions for better health outcomes. Here we describe the efforts within the Horizon 2020 EATRIS-Plus project and activities of member facilities of EATRIS towards quality assessment of pre-clinical sample processing, clinical omics data generation, multi-omics data integration, and dissemination of the resources in a Multi-Omics Toolbox, which is the principal deliverable of the EATRIS-Plus project for the consolidation of EATRIS towards translational medicine.

Aluminum chloride (AlCl3) alters the physiological response of rainbow trout - Daniela Nualart; Daniela Diaz; Jaime Tapia; Carolina Quinteros; Luis Vargas-Chacoff (Fish Physiology and Biochemistry, 2025)

Subduction transition and relation to upper plate faults revealed by the 2019 Mw 6.0 and 6.2 Costa Rica-Panama border earthquakes - Ronnie Quintero; Jiri Zahradník; Federico Güendel; Daniela Campos-Durán; Guillermo E. Alvarado; Jaime Toral Boutet (Tectonophysics, 2023)

Temporary PES do not crowd out and may crowd in lab-in-the-field forest conservation in Colombia - Lina Moros; María Alejandra Vélez; Daniela Quintero; Danny Tobin; Alexander Pfaff (Ecological Economics, 2023)

Nest architecture is linked with ecological success in songbirds - Iliana Medina; Daniela M. Perez; Ana C. Afonso Silva; Justin Cally; Constanza León; Odile Maliet; Ignacio Quintero (Ecology Letters, 2022)
Nests are essential constructions that determine fitness, yet their structure can vary substantially across bird species. While there is evidence supporting a link between nest architecture and the habitat a species occupies, we still ignore what ecological and evolutionary processes are linked to different nest types. Using information on 3175 species of songbirds, we show that—after controlling for latitude and body size—species that build domed nests (i.e. nests with a roof) have smaller ranges, are less likely to colonise urban environments and have potentially higher extinction rates compared to species with open and cavity nests. Domed nests could be a costly specialisation, and we show that these nests take more time to be built, which could restrict breeding opportunities. These diverse strands of evidence suggest that the transition from domed to open nests in passerines could represent an important evolutionary innovation behind the success of the largest bird radiation.